HUBUNGAN ANTARA PARITAS, USIA KEHAMILAN, DAN KADAR HEMOGLOBIN DENGAN BERAT BADAN LAHIR DI KLINIK BERSALIN KABUPATEN KUDUS - Saputro, Arief Adi; Rahmawaty, Annis (Institut Teknologi Kesehatan Cendekia Utama Kudus, 2024)
Background: Birth weight is an indicator of newborn health, where a baby is born healthy and full term. In general, they have a birth weight of around 3000 grams. In general, normal birth weight for a baby is between 3000 grams and 4000 grams, and if it is below or less than 2500 grams it is said to be low birth weight.Objective: To determine the relationship between parity, gestational age, and hemoglobin levels with birth weight at the Kudus Regency Maternity Clinic.Method: This research is analytical observational with a cross sectional approach using total sampling techniques.Results: There is a relationship between parity and birth weight as proven using the Spearman Rank test with a p value of 0.034 (p0.05). There is a relationship between gestational age and birth weight as proven using the Spearman Rank test with a p value of 0.000 (p0.05). There is a relationship between hemoglobin levels and birth weight as proven using the Spearman Rank test with a p value of 0.000 (p0.05)Conclusion: There is a relationship between parity, gestational age, and hemoglobin levels with birth weight.